IMPLEMENTASI PROGRAM DAERAH PEMBERDAYAAN MASYARAKAT DI KELURAHAN LOLU SELATAN KECAMATAN PALU TIMUR KOTA PALU - Rachmad, Rachmad (Katalogis, 2016)
This study aims to determine or find out now far implementation of Community Empowerment Program Policy Implementation in the Village of South Lolu District of South Palu Palu City. The method used in this research is a type of qualitative descriptive method. Determination of informants with purposive sampling technique type of data is primary data and secondary data, the technique of collecting data through observation/observation interviews/interviews, documentation and triaangulasi Based on the research that the implementation of the Program for Community Empowerment in South Lolu village of Palu, has not been fully implemented properly and not in accordance with Palu Major Regulation Number 27 Year 2013 on Guidelines for the Implementation of the Regional Program for Community Empowerment if it is associated with the theory of Van meters and Van Horn that of 6 variables that influence a policy implementation is communication between the relevant parties (stakeholders) in implematation policy experience ineffectiveness and Resources financially inadequate, Disposition program implementers and Structure Bureaucracy implementing becoming more important in application of Palu City Mayor Regulation No. 27 of 2013, which in accordance with the procedures, strategies, principles and approach to the implementation of programs and activities.